U-SERIES DISEQUILIBRIUM IN ARC MAGMAS INDUCED BY WATER-MAGMA INTERACTION - Villemant B.; Boudon G.; Komorowski J.C. (My University, 1996)
Volcanic rocks from subduction zones are widely believed to originate by partial melting of mantle lherzolite modified by the addition of a fluid or melt extracted from the down-going slab. U-series disequilibrium in such magmas is commonly attributed to this particular melting process. A detailed study of U-series isotopes in the 650 y. B.P. eruptive sequence of Mt. Pelee (Martinique) shows that plinian products are in radioactive equilibrium, whereas dome-forming products of the same eruption are characterized by 238U-230Th disequilibrium. The same features apply to other plinian and dome-forming products of this volcano and systematically correspond to different eruptive styles. We attribute these characteristics to variable superficial interaction of magmas with the hydrothermal system during the final stages of eruption rather than to deep magma genesis processes. This conclusion might be generally applicable to arc magmas.
Keywords: MOUNT PELEE; URANIUM DISEQUILIBRIUM; HYDROTHERMAL ALTERATION